EFFECTIVENESS OF APPLICATION OF COOPERATIVE LEARNING MODEL JIGSAW TYPE AND STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TYPE TOWARD MATHEMATICS LEARNING OUTCOMES IN CLASS VIII - Arum Sari Cempaka; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The application of conventional learning models in school plus student's mindset that mathematics is difficult, too many questions, too many formulas, making the lack of interest in learning mathematics of students, consequently the learning of mathematics unattractive so that influence on student learning result of the student. This study aims to determine the effectiveness of the application of cooperative learning model type Jigsaw and Student Team Achievement Division (STAD) to the results of learning mathematics. The population in Gamping (SMP Muhammadiyah 2 Gamping) Sleman Regency 2016/2017 academic year is divided into three classes, which amounts to 110 students. Two classes took samples with a random sampling technique. They obtained Class VIIIC as Experiment Class I, Class VIIIB as Experiment Class II, and Class VIIIA as Trial Class. Data analysis techniques used include a prerequisite test using normality test with Chi-Square formula, homogeneity test with F test, and hypothesis test with T-test. The results showed that: (1) There was no difference in mathematics learning results between the Jigsaw type cooperative learning model and Student Team Achievement Division (STAD). This is indicated by the value Tcount = -0.08566 <Ttable = 1.99394 at a significant level of 5% and df = 71. (2) There is nothing better between the Jigsaw type cooperative learning model and the Student Team Achievement Division (STAD) type. (3) Jigsaw cooperative learning model and Student Team Achievement Division (STAD) can improve students' mathematics learning outcomes.